ChemInform Abstract: The First Catalytic Asymmetric Cycloadditions of Imines with an Enolizable Anhydride. Issue 49 (17th November 2016) - Cronin, Sarah A.; Gutierrez Collar, Aaron; Gundala, Sivaji; Cornaggia, Claudio; Torrente, Esther; Manoni, Francesco; Botte, Astrid; Twamley, Brendan; Connon, Stephen J.
Abstract: An enantioselective cyclization of N‐mesyl aldimines with homophthalic anhydride gives 3, 4‐dihydroisoquinolin‐1‐ones.